Dietary intake and strength training management among weight sports athlete category: Role of protein intake level to body composition and muscle formation - Penggalihand, M. H. S. T.; Solichah, K. M. (Asian Journal of Clinical Nutrition, 2019)
Background and Objective: Protein has an effect on the muscle formation, but in Indonesia the fulfillment of protein and dietary intake in athletes are below the daily needs allowances. The purpose of this study is to provide recommendation intake of nutrient especially protein for weight sports athlete. Materials and Methods: There were 90 athletes as subjects participated in this experimental study. Every subjects has different calculation of nutrients needs, based on age, gender, level of activity and exercise. Recommendation for protein intake was given 1.7 g/kg of b.wt./day adjusted with strength training is considered as high protein intakes. Fats intake was 20% from total energy and carbohydrate were calculated from total energy after adjusted with energy for protein and fats. Results: The results of protein intake after intervention were found that 90 subjects are divided into 3 categories; low protein intake (Group A; <1 g/kg of b.wt./day), normal protein intake (Group B; 1-1.6 g/kg of b.wt./day) and high protein intake (Group C; >1.7 g/kg of b.wt./day). Conclusion: This study shows the correlation between high protein intake group with significant improve on subscapula and suprailiaca skinfolds. It means the body composition and muscle formations on those areas were improved followed by continuing nutritional education, especially on protein intake with the recommendation 1.7 g/kg of b.wt./day for weight sport athletes in Indonesia.